Conocimientos y prácticas del cuidador como factor asociado a enfermedad respiratoria aguda en niños de 2 meses a 5 años (2011)
ABSTRACT: To establish the relationship between Acute Respiratory Infection (ARI) and the practices and knowledge the child caregiver has. Methodology. Case-control study in which cases were children hospitalized for ARI, and controls children hospitalized for other conditions. Interviews were applied to the children’s caregivers to investigate their level of knowledge and practices related to ARI. Results. 24 cases and 24 controls were studied. The caregiver profile in both groups were women, mother of the child, housekeeper, high school level of education, members of the contributive regimen, and from socioeconomic status 2 and higher. The cases group caregivers had a lower proportion of proper IRA knowledge than controls (Cases=4.2% and controls=8.2%). Knowledge about when to consult as an emergency was proper in the 75.0% of the caregivers in the case group versus 66.7% in the control group. In the actions taken when the child has IRA, what caregivers in the control group do better is the proper management of fever, other actions had fair and poor proper management proportions. Conclusion. Caregivers Knowledge and practices were inadequate, the necessity to implement and reinforce educative actions in the community is shown.